2016
DOI: 10.3389/fict.2016.00016
|View full text |Cite
|
Sign up to set email alerts
|

How Major Depressive Disorder Affects the Ability to Decode Multimodal Dynamic Emotional Stimuli

Abstract: Most studies investigating the processing of emotions in depressed patients reported impairments in the decoding of negative emotions. However, these studies adopted static stimuli (mostly stereotypical facial expressions corresponding to basic emotions) which do not reflect the way people experience emotions in everyday life. For this reason, this work proposes to investigate the decoding of emotional expressions in patients affected by recurrent major depressive disorder (RMDD) using dynamic audio/ video sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Indeed, MDD has been associated with other physical conditions as cardiac problems and cancer [2]. Besides physical impairments, MDD also generates social disabilities, as deficits in emotional expression recognition and in personal relationships, causing isolation and pauperization of individuals' quality of life ( [3]. The MDD symptomatology consists of core and secondary symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, MDD has been associated with other physical conditions as cardiac problems and cancer [2]. Besides physical impairments, MDD also generates social disabilities, as deficits in emotional expression recognition and in personal relationships, causing isolation and pauperization of individuals' quality of life ( [3]. The MDD symptomatology consists of core and secondary symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent neuroimaging research revealed that depressed patients showed specific impairments the audiovisual integration of positive auditory stimuli (Doose-Grünefeld, Eickhoff, & Müller, 2015). Further behavioral evidence suggested that there is a general emotion processing impairment in decoding dynamic emotional audio/video stimuli (Scibelli, Troncone, Likforman-Sulem, Vinciarelli, & Esposito, 2016), and that MDD symptoms have negative effects on audiovisual integration capacity (Beatteay & Wilbiks, 2020). Recently, our group used machine learning classification models to show that MDD patients were engaged in complex functional network dysfunctions in the prefrontal cortex and limbic-subcortical areas, as well as in multisensory regions that are involved in processing audiovisual emotional stimuli (Rong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The number of people living with depressive disorders and anxiety are estimated to be the 4.4% and 3,6% of the global population respectively [5]. The manifestation of such disorders is commonly accompanied, and occasionally preceded, by the deterioration of social behavior mainly exemplified by the inability to code and decode oneself and other emotions [6] and loss of motivations such apathy, reduced feelings, lack of self-esteem, reduced social contacts. There are no established cures for depression and anxiety and treatments can last for the entire life with a consistent impoverishment of patients' quality of life and substantial increase of public cares' costs.…”
Section: Introductionmentioning
confidence: 99%